Modified high performance liquid chromatographic method for the identification of chlordiazepoxide in animal blood - Zena Sattam Hamad; Basil Mohammed Yahya (المجلة العراقية للصيدلة, 2012)
Objective: A method for simultaneous determination of chlordiazepoxide in rat plasma using liquid-liquid extraction followed by high performance liquid chromatography (HPLC) is described. Methods: The analytes were separated employing a LC-18 column (250mm×4.6mm,5µm) at ambient temperature using methanol and water (60 : 40 v/v) as a mobile phase at a flow rate 1.2 ml/min. Ultra violet (UV) detection was carried out at 254 nm. Employing liquid-liquid extraction (LLE), the best conditions were achieved with the extraction of 0.5 ml plasma using 7.5 ml deionized water, 0.5ml of 0.1M NaOH and 2.5 ml diethyl ether, the mixture was shaken for 15 min, centrifuged, and an aliquot of the ether phase evaporated off in a water bath at 30 °C. The residue was reconstituted with the mobile phase 50 µl followed by HPLC analysis. Results and conclution: This method was validated for specificity and linearity with excellent correlation coefficient (r=0.99) showed their suitable applicability in order to examine chlordiazepoxide in rat plasma.